2017
DOI: 10.1038/s41598-017-14015-6
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products promote VEGF expression and thus choroidal neovascularization via Cyr61-PI3K/AKT signaling pathway

Abstract: Choroidal neovascularisation (CNV) causes severe vision loss among old patients, especially those with diabetes. Previously, Cyr61 has been found to play a critical role in the pathogenesis of both AMD and diabetes. In the present study, we found that increased CNV severity together with higher expression of Cyr61 and VEGF in diabetes mice compared with control mice. Moreover, knockdown of Cyr61 decreased CNV severity. In vitro mechanism study revealed that the advanced glycation end products (AGEs) significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 41 publications
(12 reference statements)
2
20
0
Order By: Relevance
“…It was observed that mangiferin administration in presence of cisplatin can upregulate the expression of Nrf-2 in the renal tissue via the activation of PI3K. Previous reports also showed that mangiferin exposure only alters the expression of p-PI3K without altering the expression of total PI3K ( Qi et al, 2017 ; Zou et al, 2017 ). Besides, p-PI3K can directly upregulate the expression of Nrf-2 and can significantly promote cell survival ( Saha et al, 2016c ).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that mangiferin administration in presence of cisplatin can upregulate the expression of Nrf-2 in the renal tissue via the activation of PI3K. Previous reports also showed that mangiferin exposure only alters the expression of p-PI3K without altering the expression of total PI3K ( Qi et al, 2017 ; Zou et al, 2017 ). Besides, p-PI3K can directly upregulate the expression of Nrf-2 and can significantly promote cell survival ( Saha et al, 2016c ).…”
Section: Discussionmentioning
confidence: 99%
“…These three genes have an important role in the PI3K/AKT cell migration and proliferation related pathways. In fact, ENG and PECAM1 have a great influence over one another, and PECAM1 deficiently is associated with ENG reduction [ 56 , 57 ]. capping actin protein (CAPG) is also more highly expressed in SAT than in VAT.…”
Section: Discussionmentioning
confidence: 99%
“…; Sun et al . ). For immunoblots, lysates were separated on a 4–12% gradient sodium dodecyl sulfate‐polyacrylamide gel and transferred to a polyvinylidene fluoride membrane.…”
Section: Methodsmentioning
confidence: 97%
“…The following antibodies were selected for immunoblotting: rabbit anti-GluN1 (#G-8913, 1 : 1000; Sigma-Aldrich; RRID: AB_259978), rabbit anti-ERK1/2 (#4695, 1 : 1000; Cell Signaling Technology, Danvers, MA, USA; RRID: AB_390779), rabbit anti-p38 (#8690, 1 : 1000; Cell Signaling Technology; RRID: AB_10999090), and rabbit anti-SAPK/JNK (#9252, 1 : 1000; Cell Signaling Technology; RRID:AB_2250373). The specificity of these antibodies was validated in previous studies (Rudhard et al 2003;Brady et al 2017;Li et al 2017;Sun et al 2017). For immunoblots, lysates were separated on a 4-12% gradient sodium dodecyl sulfate-polyacrylamide gel and transferred to a polyvinylidene fluoride membrane.…”
Section: Co-immunoprecipitationmentioning
confidence: 99%